Study of some thermodynamic properties of poly[(2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate-co-butyl methacrylate] by inverse gas chromatography - Açikses, A; Kaya, I; Ilter, Z (Marcel Dekker Inc, 2003)
Some thermodynamic properties, such as the sorption enthalpy, DeltaH(1)(S); sorption free energy, DeltaG(1)(S); sorption entropy; DeltaS(1)(S); the partial molar free energy, DeltaG(1)(infinity); and the partial molar heat of mixing, DeltaH(1)(infinity); at infinite dilution were obtained for the interactions of poly [(2-phenyl-1, 3-dioxolane-4-yl)methyl methacrylate-co-butyl methacrylate] (PDMMA-co-BMA) with alcohols by the inverse gas chromatography method in a temperature range of 323 to 453degreesK. The specific retention volumes, Vg(0); the weight fraction activity coefficients of solute probes at infinite dilution, Omega(1)(infinity); and Flory-Huggins interaction parameters, chi(12)(infinity); between polymers and solvents were determined. Also, the solubility parameters, 82, of (PDMMA-co-BMA) were found to be 6.80 (cal/cm(-3))(0.5) and 7.80 (cal/cm-3)0,5 from the slope and intercept of [(delta(1)(2)/RT) - chi(12)(infinity)/V-1] = (2delta(2)/RT)delta(1) - delta(2)(2)/RT equation, at 403degreesK, respectively. The glass transition temperature, Tg, of the polymer was found to be 370 K by inverse gas chromatography.
Keywords: poly[(2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate-co-butyl methacrylate]; inverse gas chromatography; polymer-solvent interactions